2013
DOI: 10.2147/ndt.s47276
|View full text |Cite
|
Sign up to set email alerts
|

An open-label, prospective study to evaluate social function and overall improvement of extended-release paliperidone treatment in Thai schizophrenia patients

Abstract: BackgroundPrevious studies with extended-release (ER) paliperidone have reported an effective outcome in terms of personal and social functioning improvement and also reported schizophrenia symptom improvement. The main objectives of this study were to further investigate improvements in symptom control and social functioning of paliperidone ER and acknowledge the safety profile of paliperidone ER in Thai patients with schizophrenia.Patients and methodsPatients with schizophrenia according to Diagnostic and St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Previous studies have demonstrated that paliperidone ER can significantly improve social functioning, health-related quality of life, and disease severity in patients undergoing treatment for acute schizophrenia 24. Second-generation antipsychotics such as paliperidone improve social functioning by reducing psychotic symptoms with fewer adverse interactions than previously developed medications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that paliperidone ER can significantly improve social functioning, health-related quality of life, and disease severity in patients undergoing treatment for acute schizophrenia 24. Second-generation antipsychotics such as paliperidone improve social functioning by reducing psychotic symptoms with fewer adverse interactions than previously developed medications.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that paliperidone ER can significantly improve social functioning, health-related quality of life, and disease severity in patients undergoing treatment for acute schizophrenia. 2 4 Second-generation antipsychotics such as paliperidone improve social functioning by reducing psychotic symptoms with fewer adverse interactions than previously developed medications. Furthermore, a systematic review of eleven comparative studies revealed that paliperidone ER resulted in significantly greater improvements in functionality as assessed by the Personal and Social Performance Scale (PSP) than those achieved with comparative antipsychotics, including risperidone, olanzapine, and aripiprazole.…”
Section: Introductionmentioning
confidence: 99%